The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1756-185x.13157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neutrophil‐to‐lymphocyte ratio as a measure of inflammation in rheumatoid arthritis

Abstract: In contrast to the traditional markers, NLR may serve as a less expensive and effective measure of inflammation in RA. Its efficacy is comparable to that of CRP and it is not impacted by the cytokines influencing CRP and ESR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
81
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 24 publications
7
81
1
4
Order By: Relevance
“…A recent meta‐analysis showed that NLR and PLR were significantly up‐regulated in some types of rheumatic diseases including RA . Moreover, NLR and PLR were also found to be positively correlated with disease activity of RA patients, and we also found that PLR was positively correlated with CDAI and DAS28‐ESR at baseline in the present study, suggesting PLR might be used to reflect disease activity for RA patients. However, there was no significant correlation between NLR and disease activity scores, and this discrepancy might be partially owing to the different clinical and treatment background, and most of the patients included in our study had been treated with at least two cDMARDs.…”
Section: Discussionsupporting
confidence: 80%
“…A recent meta‐analysis showed that NLR and PLR were significantly up‐regulated in some types of rheumatic diseases including RA . Moreover, NLR and PLR were also found to be positively correlated with disease activity of RA patients, and we also found that PLR was positively correlated with CDAI and DAS28‐ESR at baseline in the present study, suggesting PLR might be used to reflect disease activity for RA patients. However, there was no significant correlation between NLR and disease activity scores, and this discrepancy might be partially owing to the different clinical and treatment background, and most of the patients included in our study had been treated with at least two cDMARDs.…”
Section: Discussionsupporting
confidence: 80%
“…Blood NLR, which can be calculated easily using neutrophil and lymphocyte counts, has been introduced as a potential marker for inflammation in various diseases . The negative impact of elevated NLR on clinical outcome has been noted in cardiovascular disease, cancer, liver cirrhosis, and end‐stage renal disease .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients from Western countries often used higher NLR cut‐offs than studies in patients of diverse ethnicities (e.g. Asian and African patients) . To our knowledge, no study has examined the NLR for predicting GI bleeding in Asian children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations